POLICY IMPLEMENTATION EVALUATION OF THE ENVIRONMENTAL DEVELOPMENT PROGRAM FOR IMPROVING THE ENVIRONMENTAL QUALITY: At PT. Krakatau Steel, Cilegon City - Alpano Priyandes (Program Studi Manajemen Lingkungan, 2014)
The purpose of this study is to evaluate the policy impelementation of the environmental quality in the area around Krakatau industrial estate and how the policy form of Environmental Development Programs as well as how its policy implementation process that run by PTKS. By using a qualitative method and content analysis approach to evaluate the policy implementation of Environmental Development Program, hence the result of this research indicates that the implementation of the Environmental Development Program does not run optimal particularly in the planning process and monitoring process. Therefore, the Environmental Development Program has not able to resolve the environmental problems and also social problems around the industrial area, whereas the essence of Environmental Development Program is expected to solve those problems.If the process of policy implementation of the Environmental Development Program runs properly, then it could improve the environmental quality in the area around the industrial estate. Morefor, managing the the quality of our the environment would been effectitive more.